Central Venous Catheter induced Atrial Fibrillation-A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Though a common procedure, central venous access is related to morbidity and mortality of patients. Common cardiac complications caused by central venous catheters include premature atrial and ventricular contractions. But development of atrial fibrillation with haemodynamic instability is quite rare. We are reporting a patient who developed atrial fibrillation with hypotension while inserting central venous catheter through right subclavian vein by landmark technique. Patient was managed with DC cardioversion. Careful insertion of central venous catheter & prompt management of its complication is crucial to avoid catastrophe.J Bangladesh Coll Phys Surg 2021; 39(3): 200-204